2010
DOI: 10.2337/db10-0867
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Adipose Tissue Fatty Acid Trafficking in Obesity

Abstract: OBJECTIVELipotoxicity and ectopic fat deposition reduce insulin signaling. It is not clear whether excess fat deposition in nonadipose tissue arises from excessive fatty acid delivery from adipose tissue or from impaired adipose tissue storage of ingested fat.RESEARCH DESIGN AND METHODSTo investigate this we used a whole-body integrative physiological approach with multiple and simultaneous stable-isotope fatty acid tracers to assess delivery and transport of endogenous and exogenous fatty acid in adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
291
3
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(330 citation statements)
references
References 35 publications
28
291
3
8
Order By: Relevance
“…This suggests that higher NEFA flux in postmenopausal women is a result of estrogen depletion. R a NEFA, when corrected for fat mass, was significantly lower with increasing abdominal obesity, in agreement with the concept of downregulated adipose tissue FA trafficking in obesity with reduced expression of lipolytic genes such as hormone‐sensitive lipase and adipose triglyceride lipase 44. The relationship between obesity, insulin resistance, and lipolysis is not clear in the literature and has been elegantly reviewed 45.…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that higher NEFA flux in postmenopausal women is a result of estrogen depletion. R a NEFA, when corrected for fat mass, was significantly lower with increasing abdominal obesity, in agreement with the concept of downregulated adipose tissue FA trafficking in obesity with reduced expression of lipolytic genes such as hormone‐sensitive lipase and adipose triglyceride lipase 44. The relationship between obesity, insulin resistance, and lipolysis is not clear in the literature and has been elegantly reviewed 45.…”
Section: Discussionsupporting
confidence: 71%
“…The relatively higher metabolic activity in abdominal VF fat compared with SC fat depot is well documented (34), but the metabolic potential in deep SC depots has been likened to VF fat (29,35). This metabolic similarity is attributed to the restricted capacity of peripheral fat depot to store excessive energy, leading to overflow of energy into other fat depots such as deep SC and VF compartments (36). Research has shown that adipocytes from the abdominal deep depots are metabolically superior to superficial SC compartments (29), thereby contributing significantly to global GU.…”
Section: Discussionmentioning
confidence: 96%
“…Perturbed lipid storage (20), enhanced inflammation (21,22), and altered adipokine signaling (23) have all been proposed as mechanisms for obesity-related metabolic complications. The cellular or mechanistic basis for these pathways may involve a reduced capacity to recruit and renew adipocytes, thus limiting AT expandability (24), induction of innate immune mechanisms, or the activation of cellular stress pathways (25).…”
mentioning
confidence: 99%